A New Dryland Development Paradigm Grounded in Empirical Analysis of Dryland Systems Science. (23rd June 2017) - Stringer, Lindsay C.; Reed, Mark S.; Fleskens, Luuk; Thomas, Richard J.; Le, Quang Bao; Lala‐Pritchard, Tana
Abstract: Global drylands face a host of urgent human and environmental challenges with far‐reaching impacts. Improving smallholder agriculture remains a key development pathway to tackle these challenges. The dryland development paradigm (DDP), introduced in 2007, presented a highly influential framework for dryland development based on systems research. This paper empirically derives a new, updated DDP. It assesses recent, cutting‐edge dryland science, combining literature review with qualitative and quantitative analysis of research published by the world's largest dryland science and development research initiative. The new DDP comprises eight characteristics that are distilled into three integrative principles: Unpack, Traverse and Share . The new DDP is applied and tested to identify key dryland knowledge and development gaps. A future research agenda is then elucidated, grounded in a research in development approach, in which research anchored in the three integrative principles is embedded within the context it seeks to improve. Supported by greater trans‐disciplinarity and knowledge co‐production, operationalization of the new DDP can deliver both novel scientific insights and development impact in line with the aspirations of the 2030 Sustainable Development Goals. © 2017 The Authors. Land Degradation & Development Published by John Wiley & Sons Ltd.